Analisis Jenis Ekspresif pada Akun Tiktok Shabira Alula - Emmya Ckarina Br Sembiring; Cholifia Nurchaliza; Nisreina Aura Kasih Nugraena; Pattriacia Roulina Br Malau; Rojwa Fadla Saniyya; Asep Purwo Yudi Utomo; Haris Kurnianto (Pusat riset dan Inovasi Nasional, 2024)
Pragmatics is the speaker's intention in communicating between the speaker and the speech partner. Pragmatics is related to signs (symbols) and meaning. Moris 1938 as the founder of the oldest field of pragmatics studies. Aspects in pragmatic studies are language, context, and understanding. Analysis of expressive types on Shabira Alula's TikTok account. This analysis uses a qualitative descriptive method. Expressive speech acts are the intention of the speaker's speech as an evaluation in communication. Some expressive types praise, complain, please, etc. There are types of expressiveness that are not widely known and what they mean, so the aim of this research is to find out the types of expressiveness and why they occur on Shabira Alula's TikTok account. Understanding, listening, and taking notes as data retrieval techniques. The research results show an expressive type based on Shabira Alula's TikTok account video. The benefits of this analysis are expected to know and develop each type of expressiveness. The results of the analysis based on @Shabiraalulaadnan's TikTok video show several types of expressiveness, namely comforting expressiveness, criticizing expressiveness, praising expressiveness, confusion expressiveness, apologizing expressiveness, thanking expressiveness, blaming expressiveness.